Research on Shoulder Injuries in Athletes and Treatment Methods - Kilic, Bulent; Yucel, Ali Serdar; Gumusdag, Hayrettin; Kartal, Alpaslan; Korkmaz, Murat (Kamla-Raj Enterprises, 2015)
Sports injuries have increased today due to the rise in interest towards every branch of sports. Injuries can occur in any part of the body. Sports injuries should highly be considered in terms of both the athletes' future and the medicine. This study aims to research shoulder injuries and treatment methods within the scope of upper extremity as a result of athlete injury, and accordingly to present the researchers' incidence applications. Anatomical structure of the shoulder joint and its intense usage set ground for injury. Many conservative and surgical methods exist for shoulder injuries. While some of these have become conventional (like physical therapy, and injections), some of them have become quite popular in recent years. In the researchers' clinical application for 204 athlete patients they are treated for various shoulder problems, and the methods enabled the athlete patients to return to sports in a short time through the short-range fruitful surgical applications and physiotherapy methods supported with injection. In this study, the methods used for going back to sports in a short time are explained.
Keywords: Athletes; Sports; Upper Extremity; Method; Shoulder; Treatment